Morinda officinalis polysaccharide regulates rat bone mesenchymal stem cell osteogenic–adipogenic differentiation in osteoporosis by upregulating miR‐21 and activating the PI3K/AKT pathway. Issue 7 (20th May 2022) - Wu, Pei‐Yu; Chen, Wen; Huang, He; Tang, Wang; Liang, Jie
Abstract: Osteoporosis (OP) is a prevailing bone metabolic disease. Morinda officinalis polysaccharide (MOP) has biological activities and medicinal potential. This study explored its mechanism in OP. Rat bone mesenchymal stem cells (rBMSCs) were pretreated with low/high concentrations of MOP and subjected to osteogenic differentiation (OD) or adipogenic differentiation (AD) induction. The protein markers of OD (RUNX2 and BMP2) and AD (CEBPα and PPARγ) and miR‐21 expression were detected. miR‐21 was overexpressed to study its effects on rBMSC OD and AD. rBMSCs were transfected with miR‐21 inhibitor and treated with high concentration of MOP for verification. The targeted relationship between miR‐21 and PTEN was verified by bioinformatics and dual‐luciferase assay. The PTEN/PI3K/AKT pathway‐related proteins were detected. Ovariectomy (OVX)‐induced OP rats were treated with MOP. Rat bone mineral density (BMD), serum bone metabolism indexes bone‐derived alkaline phosphatase (BALP), and osteocalcin (BGP) levels were assessed by BMD detectors and ELISA kits. miR‐21 expression in rBMSCs was detected. After treatment with low/high concentrations of MOP, the OD of rBMSCs was increased and AD was inhibited and miR‐21 was upregulated. miR‐21 overexpression enhanced the OD of rBMSCs and inhibited AD. miR‐21 knockdown reversed the effect of high concentration of MOP on rBMSCs. miR‐21 targeted PTEN. After treatment with low/high concentrations of MOP, PI3K, and AKT phosphorylation were increased and the PI3K/AKT pathway was activated. BMD, BALP, BGP, and miR‐21 levels in OVX rats were decreased. MOP partially alleviated OP in OVX rats. Briefly, MOP enhanced rBMSC OD and inhibited AD via the miR‐21/PTEN/PI3K/AKT axis.